Endothelial Progenitor Cell Migration-Enhancing Factors in the Secretome of Placental-Derived Mesenchymal Stem Cells - Witchayaporn Kamprom; Pakpoom Kheolamai; Yaowalak U-Pratya; Aungkura Supokawej; Methichit Wattanapanitch; Chuti Laowtammathron; Sittiruk Roytrakul; Surapol Issaragrisil (Stem Cells International)
Therapeutic potentials of mesenchymal stem cells (MSCs) depend largely on their ability to secrete cytokines or factors that modulate immune response, enhance cell survival, and induce neovascularization in the target tissues. We studied the secretome profile of gestational tissue-derived MSCs and their effects on functions of endothelial progenitor cells (EPCs), another angiogenic cell type that plays an important role during the neovascularization. MSCs derived from placental tissues (PL-MSCs) significantly enhanced EPC migration while BM-MSCs, which are the standard source of MSCs for various clinical applications, did not. By using protein fractionation and mass spectrometry analysis, we identified several novel candidates for EPC migration enhancing factor in PL-MSCs secretome that could be used to enhance neovascularization in the injured/ischemic tissues. We recommend that the strategy developed in our study could be used to systematically identify therapeutically useful molecules in the secretomes of other MSC sources for the clinical applications.